2020
DOI: 10.1111/dom.13951
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mean HbA1c on the association of HbA1c variability and all‐cause mortality in patients with type 2 diabetes

Abstract: Aim To evaluate the effect of mean HbA1c on the correlation between HbA1c variability and all‐cause mortality, and the risks associated with different levels of HbA1c and glycaemic control status in patients with type 2 diabetes. Materials and Methods Patients with type 2 diabetes and at least three HbA1c measurements within 12–24 months were included. HbA1c variability score, coefficient of variation (CV) and standard deviation (SD) were used to evaluate variability. A variability score of 50 was set as a cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(72 reference statements)
1
8
0
Order By: Relevance
“…In patients with type 1 diabetes, HbA1c variability was found as an important risk factor for vascular complications such as cardiovascular diseases (CVDs) [8], microvascular diseases (MVDs) [8][9][10][11], and hospitalized hypoglycemia [12]. In patients with type 2 diabetes, although cumulative evidence shows the predictive role of HbA1c variability in the risks of hypoglycemia [12], CVDs [13][14][15][16][17][18][19][20] (such as subclinical left ventricular remodeling and dysfunction [21], reduced baroreflex sensitivity [22], and high thrombotic risk [23]), and allcause mortality [15][16][17][18][19][20][24][25][26][27][28][29][30], studies on MVDs [15,19,22,[31][32][33][34][35][36][37] are relatively limited and yield inconsistent results [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with type 1 diabetes, HbA1c variability was found as an important risk factor for vascular complications such as cardiovascular diseases (CVDs) [8], microvascular diseases (MVDs) [8][9][10][11], and hospitalized hypoglycemia [12]. In patients with type 2 diabetes, although cumulative evidence shows the predictive role of HbA1c variability in the risks of hypoglycemia [12], CVDs [13][14][15][16][17][18][19][20] (such as subclinical left ventricular remodeling and dysfunction [21], reduced baroreflex sensitivity [22], and high thrombotic risk [23]), and allcause mortality [15][16][17][18][19][20][24][25][26][27][28][29][30], studies on MVDs [15,19,22,[31][32][33][34][35][36][37] are relatively limited and yield inconsistent results [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is lack of evidence for examining the comparative predictive abilities of various HbA1c variability measures for diabetic outcomes; most studies considered only one [13-15, 17, 24-28, 31-36] or two [16,29] variability measures. Although Tseng et al used three HbA1c variability measures (i.e., HbA1c-SD, HbA1c-CV, and HVS) to assess the role of mean HbA1c in the association between HbA1c variability and all-cause mortality, they did not further explore the comparative predictive abilities among these HbA1c measures [27].…”
Section: Introductionmentioning
confidence: 99%
“…18 They reported that high variability score led to higher risk of all-cause mortality and the score was less influenced by mean HbAc1 level. 18 These facts were corroborated in 2 subsequent large-scale cohort studies, 19,20 suggesting that the variability score can reflect IPV better and may be used as an alternative indicator. Learning from Forbes, we developed the Tac variability score (TVS) to define IPV and explore its impact on transplant outcomes.…”
mentioning
confidence: 81%
“…However, in patients with T2D, the cells in the liver become insulin-resistant, resulting in decreased glucose metabolism in the circulation and the outcome is hyperglycemia [10]. T2D is diagnosed using a variety of serological markers, the most prevalent of which is glycated hemoglobin (HbA1c), which is an estimated average of three months' blood glucose concentrations [11]. Dyslipidemia occurs due to abnormalities of lipid profile such as increased serum triglyceride, low-density lipoprotein-cholesterol, and decreased highdensity lipoprotein cholesterol.…”
Section: Introductionmentioning
confidence: 99%